Nonimmune hydrops fetalis: Genetic analysis and clinical outcome. (3rd May 2020) - Deng, Qiong; Fu, Fang; Yu, Qiuxia; Li, Ru; Li, Fucheng; Wang, Dan; Lei, Tingying; Yang, Xin; Liao, Can
Abstract: Objective: To investigate the genetic causes and clinical outcomes of nonimmune hydrops fetalis (NIHF). Methods: Cohort of cases of NIHF between July 2013 and December 2018. Initial genetic testing included quantitative fluorescence polymerase chain reaction for aneuploidies, karyotyping and chromosomal microarray analysis (CMA). In negative results, whole exome sequencing (WES) of the fetuses and parents was performed. Clinical post‐natal follow‐up assessments were conducted. Results: One hundred and nine patients fulfilled the study inclusion criteria and were sequentially genetically assessed by karyotype, CMA and WES. Among them, 24.8% (27/109) had a clinically significant genetic abnormality: 21 (19%) had abnormal karyotypes; 3/72 had pathogenic/likely pathogenic copy number variants (additional yield = 4.2%); and 3 had single gene disorders. The pregnancy termination and live birth rates of the cases with positive genetic testing results were significantly different from those with negative results (92.6% vs 53.7% and 3.7% vs 31.7%, respectively, P  < .05 for both). During clinical follow‐up of the survivors, 3/23 (13.0%) children developed an additional phenotype. Conclusion: This study improves our understanding of the diagnostic yield of CMA and WES for NIHF. A genetic diagnosis of NIHF can help determine the fetal prognosis and recurrence risk and influence pregnancy decision‐making.